MENINGKATKAN LOYALITAS PEGAWAI KOPI NAU DI KABUPATEN BULELENG MELALUI KEPEMIMPINAN, KOMPENSASI FINASIAL DAN MASA KERJA - DEWI, KOMANG TRISNA SARI; SUARDIKA, I KETUT; PURWANTARA, I KOMANG GDE TRISNA; SARI, GUSTI AYU DIAH KUSUMA (GANEC SWARA, 2024)
The importance of HR regulation occurs because the human element is the main actor in every operational activity of a company. Therefore HR is the main requirement to be able to carry out all activities in various organizational fields within the company. However, a number of problems were found related to leadership style, financial funding, tenure and loyalty to employees, especially employees of PT Kopi Nau Indonesia so that the examiners were interested in researching the role of "leadership style, financial compensation, and years of service on employee loyalty at PT Kopi Nau Indonesia". This test has the achievement of analyzing the role of leadership style, financial reserves, and tenure on employee loyalty at PT Kopi Nau Indonesia. The data collection technique used in this test is in the form of a questionnaire by analyzing data quantitatively using multiple linear regression analysis, tests determination, T test, F test along with qualitative analysis. The sample for this test were employees of PT Kopi Nau Indonesia Buleleng branch with a total of 75 respondents. Data analysis used multiple linear regression analysis, classical assumption test, T test analysis and F test. Based on the conclusion of the test along with its discussion, it can be concluded that leadership style, financial reserves, and years of service have a positive significant effect on employee loyalty